Technology of Orodispersible Polymer Films with Micronized Loratadine-Influence of Different Drug Loadings on Film Properties - Katarzyna Centkowska; Elżbieta Ławrecka; Malgorzata Sznitowska (MDPI AG, 2020)
The production of orodispersible films (ODFs) with suspended insoluble drug substances is still a challenge, mainly due to the difficulty associated with achieving a proper homogeneity and mechanical properties of the films. Hypromellose (HPMC) and a mixture of polyvinyl alcohol (AP) and povidone (PVP) were compared in terms of their suitability for ODFs incorporating suspended micronized loratadine (LO) in a concentration range of 10%−40%. In a planetary mixer (Thinky), a uniform dispersion of LO in an aqueous viscous casting solution was obtained. The suspended LO particles caused dose-dependent changes in the viscosity of the casting mass and affected the mechanical quality of ODFs. Drug concentrations higher than 30% reduced the film flexibility and tear resistance, depending on the polymer type. LO films with a thickness of 100 µm disintegrated within 60-100 s, with no significant influence of the LO content in the range 10%−30%. HPMC films, regardless of the drug concentration, met the pharmacopoeial requirements regarding the uniformity of the drug content. AP/PVP films were too elastic, and the drug content uniformity was not achieved. The conclusion is that, using an HPMC matrix, it is possible to obtain a high load of a poorly water-soluble drug (30% of dry film mass corresponds to a dose of 5 mg per 1.5 cm2) in ODFs characterized by proper physical characteristics.